Assessment of seed size and planting depth on seedling growth and agronomic performance of berseem (Trifolium alexandrinum) - SINGH, MAHENDRA; SINGH, TEJVEER; KANTWA, SITA RAM; RADHAKRISHNA, AUJI; KUMAR, VINOD; H S, MAHESHA; SAINI, RAVI PRAKASH (The Indian Journal of Agricultural Sciences, 2026)
Seed size and sowing depth are critical agronomic factors influencing stand establishment and productivity in forage crops, including berseem (Trifolium alexandrinum L.), a major Rabi season fodder crop This study explored the effects of seed size and sowing depth on the emergence and morphological development of berseem. Seeds were categorised into large and small seed lots to assess the impact of seed size on germination and vigor using petriplate tests.  To test the effect of sowing depth a split-plot completely randomised design in a 2 × 4 factorial arrangement, with JBSC-1 and Wardan as the main factor and four sowing depths (0.0, 2.0, 4.0 and 6.0 cm) as the sub-factor, replicated three times. Data on seedling emergence, plant height dynamics, relative chlorophyll content and biomass yield of tops and roots were measured. Large seed size showed more seedling vigor as compared to small seed irrespective of berseem. Seeds sown at the surface (0.0 cm) exhibited the highest germination percentage, followed by those sown at 2.0 cm and 4.0 cm depths. However, seeds sown at a 6.0 cm depth failed to germinate in both varieties. Sowing at a depth of 2.0 cm significantly enhanced seedling establishment, plant height and root-to-shoot ratio. Additionally, plants sown at 2.0 cm depth produced the tallest plants and superior fresh and dry leaf weights. Conversely, deeper sowing depths (4.0 cm and 6.0 cm) delayed germination and reduced plant vigor, while surface sowing and 2.0 cm depth resulted in early germination and better overall plant development. Root length and SPAD values were not significantly influenced by sowing depth. This study demonstrates that both seed size and sowing depth play a crucial role in the early establishment and growth performance of berseem. Large seeds consistently exhibited greater seedling vigor than small seeds, regardless of variety. Among the sowing depths evaluated, 2.0 cm emerged as the optimal depth, promoting superior germination, early establishment, plant height, and biomass accumulation. These insights can guide improved agronomic practices for enhancing stand establishment and fodder yield in berseem cultivation.